Nutritional Impact on Metabolic Homeostasis and Brain Health - Carneiro, Lionel; Pellerin, Luc (Frontiers in Neuroscience, 2022)
Aging in western societies is often associated with various diseases including metabolic and neurodegenerative disorders. In recent years, researchers have shown that both dysfunctions are related to each other. Although the relationship is not fully understood, recent evidence indicate that metabolic control plays a determinant role in neural defects onset. Indeed, energy balance dysregulation affects neuro-energetics by altering energy supply and thus neuronal activity. Consistently, different diets to help control body weight, blood glucose or insulin sensitivity are also effective in improving neurodegenerative disorders, dampening symptoms, or decreasing the risk of disease onset. Moreover, adapted nutritional recommendations improve learning, memory, and mood in healthy subjects as well. Interestingly, adjusted carbohydrate content of meals is the most efficient for both brain function and metabolic regulation improvement. Notably, documented neurological disorders impacted by diet adjustments suggest that the mechanisms at play involve inflammation, mitochondrial function and redox balance as well as ATP production. Interestingly, these mechanisms are also described in brain regulation of energy homeostasis. Therefore, it is likely that changes in brain function induced by diet can affect brain control of energy homeostasis and other brain functions such as memory, anxiety, social behavior or motor skills. Moreover, a defect in energy supply could participate to the development of neurodegenerative disorders. Among the possible mechanisms involved, ketone bodies metabolism, neurogenesis and synaptic plasticity, oxidative stress and inflammation or epigenetic regulations as well as gut-brain axis and SCFA have been proposed in the literature. Therefore, nutritional studies could help to better understand the tight relationship between metabolic balance, brain activity and aging. Altogether, diets that help maintaining a metabolic balance could be key to both maintain energy homeostasis and prevent neurological disorders, thus contributing to promote a healthy aging process.